Auroral Kilometric Radiation and Electron Pairing - Treumann, Rudolf A.; Baumjohann, Wolfgang (Frontiers in Physics, 2020)
We suggest that pairing of bouncing medium-energy electrons in the auroral upward current region close to the mirror points may play a role in driving the electron cyclotron maser instability to generate an escaping narrow band fine structure in the auroral kilometric radiation. We treat this mechanism in the gyrotron approximation, for simplicity using the extreme case of a weakly relativistic Dirac distribution instead the more realistic anisotropic Juettner distribution. Promising estimates of bandwidth, frequency drift and spatial location are given.